The impact of wage bargaining regime on firm-level competitiveness and wage inequality: The case of Ireland - Seamus McGuinness; Elish Kelly; Philip O'Connell (The Economic and Social Research Institute (ESRI), 2008)
This paper uses a linked employer-employee dataset to analyse the impact of institutional wage bargaining regimes on levels of average labour costs and within firm wage dispersion in private sector companies in Ireland. The results show that while centralised bargaining reduced labour costs within both the indigenous and foreign-owned sectors, the relative advantage was greater among foreign-owned firms. The analysis suggests that there are potentially large competitiveness gains to multinational companies that choose to locate in countries implementing a centralised bargaining system. Furthermore, the results provide additional support to the view that collective bargaining reduces within firm wage inequality.
Keywords: J51; J52; J58; 330; wage bargaining regimes; labour costs; wage dispersion; Ireland; Lohnverhandlungen; Lohnpolitik; Unternehmensentwicklung; Wettbewerb; Lohndrift; Irland